Analisis Digital Artifak Aplikasi Signal Messenger Pada Sistem Operasi Android dengan metode NIST - Nafila, Feryan Lutfie; prayudi, Yudi (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
Message applications have now become a part of today's society. Beside from features, security and privacy are important things for users. Security and privacy are important because some users of this application are worried if the message their send will misused by the company. This concern is heightened after a new rule issued by a popular instant messaging application company where data from the messaging application will be linked to other applications for business purposes, some popular messenger users are worried about their privacy choosing to switch to other messaging applications that are considered more secure and offers privacy. One of the applications of choice is Signal Messenger becouse this application is more secure in maintaining privacy. This is a concern if applications that offer more privacy become a means to commit crimes. Consider that, the research work will focused on conducting forensic testing and analysis of the Android-based Signal Messenger application. The test will carried out on SMA530F and RedmiNote 4 smartphone devices. The scenario that will applied is by installing the Signal Messenger application on each smartphone, then communication between the two smartphones is such as sending text messages, images, and videos. From these activities, the mobile forensics stage using the NIST method such as making acquisitions and then analysis to obtain digital evidence. The test results will be expect for a reference for the authorities and related parties if there is a case using the Signal Messenger application and it is hoped that this research can add to the literature in the field of digital forensics, especially mobile forensics